2005
DOI: 10.1590/s1519-566x2005000100022
|View full text |Cite
|
Sign up to set email alerts
|

Patogenicidade de Steinernema glaseri e S. carpocapsae (Nematoda: Rhabdita) contra o cascudinho, Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae)

Abstract: Pathogenicity of Steinernema glaseri and S. carpocapsae (Nematoda: Rhabdita) against the Lesswer Mealworm, Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae)ABSTRACT -The lesser mealworm, Alphitobius diaperinus (Panzer), is an important pest in poultry production systems. Due to the lack of effective and safe tactics to control this insect the interest on developing alternative control tactics such as microbial control has increased. The pathogenicity of entomopathogenic nematodes (Steinernematidae) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
1
5
0
3
Order By: Relevance
“…Larvae and adults of A. diaperinus show active movement in chicken litter bedding in poultry farms; therefore, the ambusher behavior can be considered an ecological adaptation that would favor A. diaperinus control. Mortality values of A. diaperinus larvae caused by S. rarum obtained in the present study are close to values reported for S. carpocapsae (Alves et al 2005;Pezowicz et al 2013), a species with ambusher foraging strategy (Campbell and Gaugler 1993).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Larvae and adults of A. diaperinus show active movement in chicken litter bedding in poultry farms; therefore, the ambusher behavior can be considered an ecological adaptation that would favor A. diaperinus control. Mortality values of A. diaperinus larvae caused by S. rarum obtained in the present study are close to values reported for S. carpocapsae (Alves et al 2005;Pezowicz et al 2013), a species with ambusher foraging strategy (Campbell and Gaugler 1993).…”
Section: Discussionsupporting
confidence: 90%
“…The potential of EPNs for suppressing A. diaperinus is well documented (Alves et al 2005(Alves et al , 2012Geden et al 1985Geden et al , 1987Szalanski et al 2004). However, the diversity of materials used to prepare chicken litter in poultry systems worldwide and the heterogeneity of microenvironments generated in poultry facilities show the need for further research (Benabdeljelil and Ayachi 1996;Garcia et al 2012;Runge et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…donde se indujo la formación de raicillas, sobre estos se colocó una ninfa de A. albofasciata. La inoculación se llevó a cabo aplicando una sola concentración de juveniles infectivos, 120 JI cm -2 de acuerdo a Alves et al (2005). La aplicación se realizó sobre el papel filtro, permitiendo el desplazamiento de los JI y búsqueda del insecto hospedero.…”
Section: Procedimiento Experimentalunclassified
“…In addition, the uninterrupted presence of birds in the aviary and the insect's habit of sheltering in wall cracks, floor cracks, underneath feeders, drinking fountains, near the support pillars of the constructions, and below ground hinders control and favors reinfestations (Alves et al, 2005). The insects are usually controlled by applications of chemical insecticides on the poultry litter surface and soil (Dias et al, 2013).…”
Section: Introductionmentioning
confidence: 99%